The role of auditor independence, integrity, competence and professionalism in improving audit quality to strengthen government transparency and accountability - Dito Aditia Darma Nst; Siti Nur Fadhilah Nasution; Annisa Syahrani; Prilia Astari (Economic: Journal Economic and Business, 2026)
Transparency and accountability are key principles of good governance, particularly in the management of state finances. Public sector audits play a strategic role in ensuring the reliability of government financial reports and enhancing public trust. However, the paradox of audit quality is still common, where government entities obtain an Unqualified Opinion (WTP) but still face financial irregularities. This situation indicates that audit quality is determined not only by the audit results but also by the characteristics of the auditor. This study aims to examine the role of auditor independence, integrity, competence, and professionalism in improving audit quality and their implications for strengthening government transparency and accountability. The research method used is a literature review by analyzing audit textbooks, national scientific journals, and regulations related to public sector audits descriptively and critically. The study results indicate that auditor independence and integrity are the main foundations in maintaining the objectivity and credibility of audits, while competence and professionalism play a role in ensuring the accuracy of audit procedures and the quality of recommendations. These four factors simultaneously improve audit quality and contribute significantly to strengthening transparency and accountability in government financial management.